Anti-VEGF-therapy for pseudoxanthoma elasticum (case reports) - A.D. Chuprov; S.M. Kim; E.A. Pidodniy; A.M. Iserkepova (РМЖ "Клиническая офтальмология")
A.D. Chuprov, S.M. Kim, E.A. Pidodniy, A.M. Iserkepova Orenburg Branch of the S. Fyodorov Eye Microsurgery Federal State Institution, Orenburg, Russian Federation Pseudoxanthoma elasticum (PXE), also known as Gröenblad-Strandberg syndrome, is a rare autosomal recessive disease affecting the skin, eyes, gastrointestinal tract, and cardiovascular system. The disease is caused by a defect in ABCC 6 (adenosine triphosphate-binding cassette, subfamily C, member 6) transporter involved in the homeostasis of serum pyrophosphate, the key inhibitor of ectopic calcification. Dysfunction or lack of ABCC 6 leads to a decrease in serum pyrophosphate levels and, as a result, ectopic calcification of soft connective tissue. Skin lesions in PXE are flat yellowish xanthomatous nodules of various shapes and sizes. The leading signs of eye disorder are angioid streaks and choroidal neovascularization (CNV). Progressive destruction of Bruch's membrane favors CNV, whereas macular neovascularization is the key reason for a reduction in central vision in PXE. Intravitreal injection of anti-VEGF medications is a promising treatment for CNV due to angioid bands. Ranibizumab is approved for CNV of various origins, including CNV due to angioid streaks. This paper addresses clinical observations illustrating the efficacy of anti-VEGF therapy for pseudoxanthoma elasticum. Keywords: Gröenblad-Strandberg syndrome, angioid streaks, choroidal neovascularization, pseudoxanthoma elasticum, VEGF inhibitors. For citation: Chuprov A.D., Kim S.M., Pidodniy E.A., Iserkepova A.M. Anti-VEGF-therapy for pseudoxanthoma elasticum (case reports). Russian Journal of Clinical Ophthalmology. 2023;23(3):157–163 (in Russ.). DOI: 10.32364/2311-7729-2023-23-3-8.